Judgments, Orders and Advisory Opinions: Vol. 14, 1938 - International Court of Justice (United Nations, 1938)
Any legal library would be incomplete without the entire set of this historical reprint of the decisions of the Permanent Court of International Justice. The 15 bound volumes include Judgments from 1923-1930 (Series A), Advisory Opinions from 1923-1930 (Series B) and Judgments, Orders and Advisory Opinions from 1931-1940 (Series A/B). Volume 14 contains the Phosphate in Morocco Judgment and two Orders from the Borchgrave and Panevezys-Saldutiskis Railway cases.